Molecular evidence for cryptic species in Pteroclava krempfi (Hydrozoa, Cladocorynidae) living in association with alcyonaceans. Issue 5 (2nd September 2016) - Maggioni, Davide; Montano, Simone; Seveso, Davide; Galli, Paolo
Abstract : Hydrozoans are able to establish intimate relationships with several other organisms. The hydroid Pteroclava krempfi lives in association with different alcyonacean taxa from Indo-Pacific and Atlantic coral reefs, growing partially embedded within host tissues. In this study, we found P. krempfi associated with four alcyonacean hosts from the Maldives, namely Sinularia, Sarcophyton, Lobophytum and Paraplexaura, the latter representing a new record. We provided the first molecular phylogenetic evaluation of the genus Pteroclava . Pteroclava krempfi clustered with Cladocoryne floccosa, confirming its position into the family Cladocorynidae. We also performed the first morpho-molecular assessment of P. krempfi diversity. All the colonies growing on different hosts revealed polyps and medusae matching published descriptions of P. krempfi, showing no morphological differences. However, analysing both nuclear and mitochondrial DNA, two highly supported molecular lineages were identified. These two clades were highly divergent and were specifically associated with hosts belonging to different families (Alcyoniidae and Plexauridae). Therefore, our results suggest that P. krempfi from the Maldives is a complex of cryptic species in which the main diagnostic feature between different species could be the host specificity.